Cafeina-Mateina, La presencia del café y el mate en la vid cotidiana (2021)
In other words, a reality is built from the collective interactions of everyday life; based on knowledge, beliefs, norms. A representation can become a perception of a concrete concept that is present in the minds of all people. Thus the observation and appropriation of two interactions located in the cultures of Colombia and Argentina, represented in the consumption of two traditionally used stimulating drinks configure a thematic approach to the project and lead to the imaginary of creation of work in order to create from the experiences acquired compositions that unite these two cultures by making them one through the form and the image. Where the senses allow a journey based on experiences acquired towards the path of integration as an ethnographer. The concern of formulating CAFFEINE-MATEINE was born, as the name of my creation research project. This project idea arises from the acquired own experiences allowed thanks to the continuous integration in two cultures; in this case of Colombia as a native country and Argentina as a country of origin. new encounters of knowledge acquired from everyday life. exploring various materials such as clay, plasticine, flour, soap, photography, video, animation, performance.